Developing Communicative Competence in Uzbek for International Students (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines strategies for fostering communicative competence in the Uzbek language among international students, a growing demographic due to Uzbekistan’s expanding global educational and cultural partnerships. The study explores effective pedagogical approaches that integrate task-based language teaching and cultural immersion to enhance learners’ communicative abilities. Employing a mixed-methods design—comprising both quantitative assessments and qualitative interviews—the research highlights significant improvements in linguistic and pragmatic skills among participants. The findings emphasize the importance of context-rich, interactive instruction and provide practical recommendations for curriculum development aimed at international learners of Uzbek.